High-reflection high-transmittance top coating film and preparation method thereof
By adopting a high reflective and high-transmissive top coating design in the explosion-proof film inside the back cover of the mobile phone, including protective film layer, primer layer, substrate layer, printable HC layer, composite structural layer, OCA optical adhesive layer and release film layer , solve the problems of low reflectivity and insufficient hardness in the prior art, and achieve efficient explosion-proof and optical performance.
Patent Information
- Application Number
- CN202411530392.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-18
AI Technical Summary
The processing technology of the explosion-proof film inside the back cover of the existing mobile phone has problems such as low reflectivity, insufficient hardness, and haze. It is easy to have poor molar patterns during the preparation process, which affects the product yield.
A high reflective and high-transmissive top coating is adopted, which includes a protective film layer, a primer layer, a base material layer, a printable HC layer, a composite structural layer, an OCA optical adhesive layer and a release film layer arranged in sequence from top to bottom , the composite structural layer is formed through magnetron sputtering coating process, and the OCA optical adhesive layer and release film layer are combined to improve the optical performance and adhesion of the film.
It realizes high reflective and high transmission optical performance, avoids glass splash caused by breaking the back cover of the mobile phone, and improves the adhesion and cracking performance of the explosion-proof film, solving the low reflectivity and insufficient hardness in the prior art. The problem.
Smart Images

Figure CN119463720A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of explosion-proof film materials, and in particular to a high-reflection and high-transmittance top coating and a preparation method thereof. Background Art
[0002] With the continuous development of mobile phone manufacturing technology, higher requirements are put forward for signal transmission. Traditional metal shells have a certain shielding effect on signal transmission, which has promoted the application and development of glass mobile phone cases. Nowadays, mobile phone terminals such as Huawei, Xiaomi, OPPO, and VIVO all use 2.5 / 3D glass mobile phone cases. However, the glass shell has poor drop resistance and explosion resistance, and is easily damaged during use. Therefore, at this stage, a protective film is usually introduced in the process of mobile phone preparation to solve this problem. In view of this, higher requirements are put forward for the protective film, which must have good protection effects while also meeting visual and optical effects.
[0003] The explosion-proof film inside the back cover of the mobile phone, also known as the top coating, is a protective film used on the glass back cover of the mobile phone battery, which effectively alleviates the shattering and splashing of the back cover glass panel caused by the collision of the mobile phone with other objects. If there is no explosion-proof film inside the back cover of the mobile phone, the glass will splash in all directions after breaking, so the explosion-proof film inside the back cover of the mobile phone can reduce the unsafe factors of the glass panel and further improve the safety performance; at the same time, it also has optical effects such as high brightness and high reflection.
[0004] At present, the main processing technology of explosion-proof film inside the back cover of mobile phones is GDF: coating OCA on the PET base film, and then performing back-end processing: UV lighting, coating, printing and other steps to obtain a product that meets the requirements. However, this process has problems such as low reflectivity, insufficient hardness, and high haze during the preparation of the inner film of the back cover; and moiré defects are prone to occur during the preparation process, which affects the yield of the product.
[0005] Therefore, it is necessary to improve the existing technology to provide a more reliable solution. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a high-reflection and high-transmittance top coating and a preparation method thereof in view of the deficiencies in the above-mentioned prior art.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a high-reflection and high-transmittance top coating, including a protective film layer, a primer layer, a substrate layer, a printable HC layer, a composite structure layer, an OCA optical adhesive layer and a release film layer stacked in sequence from top to bottom.
[0008] Preferably, the composite structure layer is obtained by magnetron sputtering coating on the lower surface of the printable HC layer, and the composite structure layer includes a primer layer, a first niobium oxide layer, a first silicon dioxide layer, a second niobium oxide layer, a second silicon dioxide layer, a third niobium oxide layer and a silicon-aluminum mixed layer stacked in sequence from top to bottom;
[0009] The molar ratio of silicon to aluminum in the silicon-aluminum mixed layer is 80-95:20-5.
[0010] Preferably, the total thickness of the composite structure layer is between 30nm-100nm, and the refractive index is between 1.90-2.30;
[0011] The thickness of the base layer is 0.1-1nm, the thickness of the first niobium oxide layer is 5-30nm, the thickness of the first silicon dioxide layer is 3-16nm, the thickness of the second niobium oxide layer is 5-20nm, the thickness of the second silicon dioxide layer is 3-10nm, the thickness of the third niobium oxide layer is 5-10nm, and the thickness of the silicon-aluminum mixed layer is 2-10nm.
[0012] Preferably, the selected protective film layer is a PET protective film with a thickness of 25 μm-100 μm;
[0013] The thickness of the primer layer is 0.1 μm-0.9 μm.
[0014] Preferably, the substrate layer is selected from a PET layer, a PI layer, a TAC layer, a COP layer, and a PC layer; and the thickness of the substrate layer is 25-100 μm.
[0015] Preferably, the printable HC layer is a polyurethane acrylic resin film layer with a thickness of 1 μm-9 μm.
[0016] Preferably, the OCA optical adhesive layer is obtained by coating OCA adhesive on the composite structure layer, and the OCA adhesive includes the following raw materials in parts by weight: 60-120 parts of acrylic prepolymer; 0.1-0.4 parts of first photoinitiator; 0.1-0.3 parts of leveling agent; 0.2-0.5 parts of coupling agent; and 0.1-0.4 parts of cross-linking agent.
[0017] Preferably, the acrylic prepolymer comprises the following raw materials in parts by weight: 45-75 parts of isooctyl acrylate; 15-35 parts of 2-hydroxyethyl acrylate; 5-22 parts of isobornyl acrylate; 5-15 parts of acrylic acid; 0.02-1 parts of a second photoinitiator; and 0.02-1 parts of a molecular weight regulator.
[0018] Preferably, the thickness of the OCA optical adhesive layer is 5 μm-50 μm; and the thickness of the release film is between 100 μm-200 μm.
[0019] The present invention also provides a method for preparing the high-reflection and high-transmittance top coating as described above, comprising the following steps:
[0020] S1. A primer layer and a printable HC layer are respectively coated on the upper surface and the lower surface of the substrate layer, and a protective film layer is attached to the upper surface of the primer layer;
[0021] S2. Using a magnetron sputtering coating process, selecting argon gas to bombard the target material, and sequentially coating a primer layer, a first niobium oxide layer, a first silicon dioxide layer, a second niobium oxide layer, a second silicon dioxide layer, a third niobium oxide layer and a silicon-aluminum mixed layer on the lower surface of the printable HC layer to form a composite structure layer;
[0022] S3, coating the lower surface of the silicon-aluminum mixed layer of the composite structure layer with OCA glue, and forming an OCA optical glue layer after curing;
[0023] S4, laminating a release film layer on the lower surface of the OCA optical adhesive layer to obtain the high-reflection and high-transmittance top coating.
[0024] The beneficial effects of the present invention are:
[0025] 1. The present invention provides a high-reflection and high-transmittance top coating and a preparation method thereof. The top coating of the present invention can prevent glass splashing caused by external impact on the back cover of a mobile phone, and has good optical and visual effects. The present invention adopts a new coating process to design the interlayer structure of the explosion-proof film, and the different coatings are well connected and matched, which can achieve performance goals while solving the problem of single appearance.
[0026] 2. The present invention performs PVD sputtering treatment on an optical PET substrate, and by adjusting the process parameters of the equipment, selecting a suitable refractive index, and setting the type and thickness of each structural layer in the sputtered composite layer, a structural layer with a thickness of 30nm-100nm is obtained, which has high reflective and high transmittance optical properties, and can improve the mirror effect of the explosion-proof film; while ensuring high reflective performance, it can take into account the optical properties of the explosion-proof film such as high transmittance and low fog; and at the same time has good adhesion and anti-cracking performance.
[0027] 3. Before PVD treatment, due to the insufficient hardness and uniformity of the substrate, wrinkling and shrinkage are likely to occur during PVD sputtering, resulting in poor uniformity and density of the coating layer. Therefore, the PET substrate needs to be treated before PVD sputtering. In the present invention, the HC hardening layer is first coated on the sputtering surface, which can improve the surface properties of the substrate and ensure the adhesion between the substrate and the PVD coating and the density of the coating.
[0028] 4. The present invention affixes a protective film layer on the other side of the substrate layer, which provides good support and protection for the substrate. It works synergistically with the HC hardening layer to ensure the flatness and hardness of the film material during PVD sputtering, and to ensure the uniformity and stability of the coating effect. The substrate layer and the protective film layer are bonded by primer, which can match most UV transfer adhesives.
[0029] 5. The self-synthesized OCA optical adhesive used in the present invention has high transmittance and low haze, and has excellent bonding effect on a variety of plates, while taking into account the performance of all-around measurement, large-angle bonding without rebound, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic structural diagram of the high-reflection and high-transmittance top coating of the present invention;
[0031] Figure 2 It is a schematic structural diagram of the composite structural layer of the present invention;
[0032] Figure 3 It is the reflectivity spectrum curve of embodiment and comparative example.
[0033] Description of reference numerals:
[0034] 1—protective film layer; 2—primer layer; 3—substrate layer; 4—printable HC layer; 5—composite structure layer; 6—OCA optical adhesive layer; 7—release film layer; 51—priming layer; 52—first niobium oxide layer; 53—first silicon dioxide layer; 54—second niobium oxide layer; 55—second silicon dioxide layer; 56—third niobium oxide layer; 57—silicon-aluminum mixed layer. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0036] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0037] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0038] The present invention provides a high-reflection and high-transmittance top coating, comprising a protective film layer 1, a primer layer 2, a substrate layer 3, a printable HC layer 4, a composite structure layer 5, an OCA optical adhesive layer 6 and a release film layer 7 stacked in sequence from top to bottom.
[0039] The upper surface of the substrate layer 3 is bonded with a protective film layer 1 through a primer layer 2 to ensure the appearance of the film and the stability of the coating during the magnetron sputtering coating process. In a preferred embodiment, the selected protective film layer 1 is a PET protective film with a thickness of 25 μm-100 μm; the PET protective film has high transparency, chemical resistance, and scratch resistance, and can improve the working stability and reliability of the substrate.
[0040] The base material layer 3 and the protective film layer 1 are bonded together using a primer, which can ensure that most of the UV transfer glue is applied. In a preferred embodiment, the thickness of the primer layer 2 is 0.1 μm-0.9 μm.
[0041] In a preferred embodiment, the substrate layer 3 is selected from a PET layer, a PI layer, a TAC layer, a COP layer, and a PC layer; and the thickness of the substrate layer 3 is 25-100 μm.
[0042] In a preferred embodiment, the printable HC layer 4 is a polyurethane acrylic resin film layer, which is beneficial to improving the surface properties of the substrate layer 31 and preventing the substrate from wrinkling, shrinking, etc. during subsequent steps. Further, its thickness is 1 μm-9 μm.
[0043] In a preferred embodiment, the composite structure layer 5 is obtained by magnetron sputtering coating on the lower surface of the printable HC layer 4, and the composite structure layer 5 includes a base layer 51, a first niobium oxide layer 52, a first silicon dioxide layer 53, a second niobium oxide layer 54, a second silicon dioxide layer 55, a third niobium oxide layer 56 and a silicon-aluminum mixed layer 57 stacked in sequence from top to bottom.
[0044] Niobium oxide has good optical properties, with high refractive and low dispersion characteristics; silicon dioxide has good light transmittance, high refractive index and low scattering; and niobium oxide and silicon dioxide have good stability, are not easy to react with acids and alkalis, and can still maintain good optical properties at high temperatures. The silicon-aluminum ratio in the silicon-aluminum mixed target refers to the molar ratio. Different silicon-aluminum ratios will affect the reflection effect of the silicon-aluminum mixed layer 57. By selecting a specific silicon-aluminum ratio, the silicon-aluminum mixed layer 57 can present the advantages of high transmittance, high reflection and high heat resistance.
[0045] In a preferred embodiment, the molar ratio of silicon to aluminum in the silicon-aluminum mixed layer 57 is 80-95:20-5.
[0046] In a preferred embodiment, the total thickness of the composite structure layer 5 is between 30nm and 100nm, and the refractive index is between 1.90 and 2.30;
[0047] In a preferred embodiment, the thickness of the primer layer 51 is 0.1-1 nm, the thickness of the first niobium oxide layer 52 is 5-30 nm, the thickness of the first silicon dioxide layer 53 is 3-16 nm, the thickness of the second niobium oxide layer 54 is 5-20 nm, the thickness of the second silicon dioxide layer 55 is 3-10 nm, the thickness of the third niobium oxide layer 56 is 5-10 nm, and the thickness of the silicon-aluminum mixed layer 57 is 2-10 nm. By setting the thickness of each layer, it is beneficial to adjust the reflectivity and refractive index of the sample so that the optical performance meets the requirements. The composite structure layer 5 is sputtered on the substrate coated with the printable HC layer 4 by magnetron sputtering, and different structure layers cooperate with each other to achieve the adjustment of the reflectivity of the coating layer.
[0048] In a preferred embodiment, the OCA optical adhesive layer 6 is obtained by coating OCA adhesive on the composite structure layer 5, and the OCA adhesive includes the following raw materials in parts by weight: 60-120 parts of acrylic prepolymer; 0.1-0.4 parts of a first photoinitiator; 0.1-0.3 parts of a leveling agent; 0.2-0.5 parts of a coupling agent; and 0.1-0.4 parts of a cross-linking agent.
[0049] In a preferred embodiment, the acrylic prepolymer comprises the following raw materials in parts by weight: 45-75 parts of isooctyl acrylate; 15-35 parts of 2-hydroxyethyl acrylate; 5-22 parts of isobornyl acrylate; 5-15 parts of acrylic acid; 0.02-1 parts of a second photoinitiator; and 0.02-1 parts of a molecular weight regulator.
[0050] In a preferred embodiment, the thickness of the OCA optical adhesive layer 6 is 5 μm-50 μm.
[0051] In a preferred embodiment, the thickness of the release film is between 100 μm and 200 μm.
[0052] The present invention also provides a method for preparing the high-reflection and high-transmittance top coating as described above, comprising the following steps:
[0053] S1, coating the upper surface and lower surface of the substrate layer 3 to form a primer layer 2 and a printable HC layer 4, respectively, and laminating the protective film layer 1 on the upper surface of the primer layer 2 to ensure the appearance of the material and the stability of the coating during the magnetron sputtering coating process;
[0054] S2, using a magnetron sputtering coating process, selecting argon gas to bombard the target material, and sequentially coating a base layer 51, a first niobium oxide layer 52, a first silicon dioxide layer 53, a second niobium oxide layer 54, a second silicon dioxide layer 55, a third niobium oxide layer 56 and a silicon-aluminum mixed layer 57 on the lower surface of the printable HC layer 4 to form a composite structure layer 5;
[0055] In order to ensure the effect of the PVD coating layer, a protective film layer 1 needs to be attached to the untreated side of the substrate layer 3 before sputtering. Furthermore, the protective film layer 1 is a high-cleanliness, low-transfer, and temperature-resistant protective film with a thickness of 50 μm-100 μm. If the protective film layer 1 is not provided, the substrate layer 3 will wrinkle and shrink, the coating will be uneven, and the density will be poor during the sputtering process, which will affect the final effect of the sample.
[0056] S3, coating the lower surface of the silicon-aluminum mixed layer 57 of the composite structure layer 5 with OCA glue, and forming an OCA optical glue layer 6 after curing;
[0057] S4, laminating the release film layer 7 on the lower surface of the OCA optical adhesive layer 6 to obtain the high-reflection and high-transmittance top coating.
[0058] Through the structural design between layers, the top coating finally prepared has a good explosion-proof effect, avoiding the glass splashing caused by the broken mobile phone case. At the same time, by setting the process parameters to adjust the thickness and reflectivity of the PVD high-reflective coating, it is convenient to reduce the coating thickness during the secondary sputtering at the back end, making the overall thickness of the explosion-proof film lighter and thinner.
[0059] The present invention also provides an application method of the high-reflection and high-transmittance top coating as described above, which is as follows: after the protective film layer 1 is peeled off, the explosion-proof film is continuously subjected to ultraviolet printing, coating and other treatments at the rear end to improve the color effect of the explosion-proof film and enable the explosion-proof film to obtain the target color. When in use, the release film outside the OCA optical adhesive layer 6 is peeled off, and the high-reflection and high-transmittance top coating is closely attached to the back cover of the glass mobile phone under the high viscosity of the OCA optical adhesive layer 6, thereby playing the role of the explosion-proof film.
[0060] The high-reflection and high-transmittance top coating of the present invention uses the printable HC layer 4, the composite structure layer 5 and the OCA adhesive layer as functional layers, and the requirements of the top coating of the terminal device are met by setting the functional layers.
[0061] The top coating of the present invention should not only be able to prevent splashing after the glass back cover explodes, but also meet good visual and optical effects; the excellent interlayer structure design of the present invention can maximize the role of each functional layer through good connection and coordination between different coatings to ensure the performance of the explosion-proof film. The present invention uses PVD coating technology to coat the composite structure layer 5 on the surface of the PET substrate to enhance the mirror effect of the explosion-proof film, so that the explosion-proof film inside the back cover has excellent adhesion and anti-cracking performance while meeting good optical performance.
[0062] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0063] OCA glue was prepared in advance for use in the following examples and comparative examples, and the preparation method was as follows:
[0064] 1. Preparation of acrylic acid prepolymer:
[0065] Weigh the following raw materials by weight:
[0066] 63.5 parts of 2-isooctanoate acrylate, 25 parts of 2-hydroxyethyl acrylate, 5 parts of isobornyl acrylate, 5 parts of acrylic acid; 0.5 parts of the second photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone); 1 part of molecular weight regulator (n-dodecyl mercaptoethanol);
[0067] The above raw materials were added into a reaction kettle according to the proportion, stirred evenly under the protection of nitrogen atmosphere, and irradiated with UV ultraviolet light to cause free radical polymerization reaction, with the ultraviolet wavelength of 350nm, to obtain an acrylic prepolymer with a viscosity of 8000mPa.s.
[0068] 2. Preparation of OCA glue:
[0069] Calculated by weight percentage, 98.9wt% of acrylic prepolymer, 0.2wt% of photoinitiator (photoinitiator 184, i.e. 1-hydroxycyclohexyl phenyl ketone), 0.1wt% of leveling agent (BYK377), 0.4wt% of coupling agent (silane coupling agent KH560), and 0.4wt% of cross-linking agent (1,4-butanediol diacrylate) are added into a glass reactor in sequence, and stirred evenly at room temperature to obtain OCA optical adhesive.
[0070] Example 1
[0071] A high-reflection and high-transmittance top coating, comprising a protective film layer 1, a primer layer 2, a substrate layer 3, a printable HC layer 4, a composite structure layer 5, an OCA optical adhesive layer 6 and a release film layer 7 which are stacked in sequence from top to bottom;
[0072] The preparation method comprises the following steps:
[0073] S1. A primer layer 2 and a printable HC layer 4 are coated on the upper and lower surfaces of the substrate layer 3, respectively, and a protective film layer 1 is attached to the upper surface of the primer layer 2; wherein the primer is a commercially available product, aqueous polyurethane emulsion YS-1660, purchased from Yingshuo Chemical, and the primer layer is obtained by drying after coating.
[0074] S2, using a magnetron sputtering coating process, selecting argon gas to bombard the target material, and sequentially coating a base layer 51, a first niobium oxide layer 52, a first silicon dioxide layer 53, a second niobium oxide layer 54, a second silicon dioxide layer 55, a third niobium oxide layer 56 and a silicon-aluminum mixed layer 57 on the lower surface of the printable HC layer 4 to form a composite structure layer 5;
[0075] S3, coating the lower surface of the silicon-aluminum mixed layer 57 of the composite structure layer 5 with OCA glue, and heat-curing at 120° C. for 3 minutes to form an OCA optical glue layer 6;
[0076] S4, laminating the release film layer 7 on the lower surface of the OCA optical adhesive layer 6 to obtain the high-reflection and high-transmittance top coating.
[0077] In this embodiment, the substrate layer 3 is a PET layer with a thickness of 50 μm; the primer layer 2 is 0.1 μm thick; the protective film layer 1 is a PET protective film with a thickness of 100 μm, and the protective film layer 1 and the substrate layer 3 are bonded together using a primer; the printable HC layer 4 is a polyurethane acrylic resin film layer with a thickness of 7 μm.
[0078] In this embodiment, the composite structure layer 5 has a thickness of 79.8 nm, the base layer 51 is made of silicon with a thickness of 1 nm; the first niobium oxide layer 52 has a thickness of 24.5 nm, the first silicon dioxide layer 53 has a thickness of 15.3 nm; the second niobium oxide layer 54 has a thickness of 15 nm; the second silicon dioxide layer 55 has a thickness of 9.0 nm; the third niobium oxide layer 56 has a thickness of 7.5 nm; the silicon-aluminum mixed layer 57 has a thickness of 7.5 nm, and the molar ratio of silicon to aluminum in the silicon-aluminum mixed layer 57 is 81.5:18.5.
[0079] In this embodiment, the thickness of the OCA layer is 20 μm, and the thickness of the release film layer 7 is 50 μm.
[0080] Example 2
[0081] The difference between this embodiment and embodiment 1 is that the thickness of the composite structure layer 5 is set differently, as follows:
[0082] The composite structure layer 5 in this example has a thickness of 67.9 nm, the base layer 51 is made of silicon with a thickness of 1 nm; the first niobium oxide layer 52 has a thickness of 24.5 nm, the first silicon dioxide layer 53 has a thickness of 12.0 nm; the second niobium oxide layer 54 has a thickness of 13.2 nm; the second silicon dioxide layer 55 has a thickness of 6.5 nm; the third niobium oxide layer 56 has a thickness of 5.2 nm; the silicon-aluminum mixed layer 57 has a thickness of 5.5 nm, and the molar ratio of silicon to aluminum in the silicon-aluminum mixed layer 57 is 81.5:18.5.
[0083] Example 3
[0084] The difference between this embodiment and embodiment 1 is that the thickness of the composite structure layer 5 is set differently, as follows:
[0085] The composite structure layer 5 in this example has a thickness of 65.5 nm, the base layer 51 is made of silicon with a thickness of 0.5 nm; the first niobium oxide layer 52 has a thickness of 27.5 nm, the first silicon dioxide layer 53 has a thickness of 6.0 nm; the second niobium oxide layer 54 has a thickness of 15.0 nm; the second silicon dioxide layer 55 has a thickness of 6.5 nm; the third niobium oxide layer 56 has a thickness of 7.0 nm; the silicon-aluminum mixed layer 57 has a thickness of 2.5 nm, and the molar ratio of silicon to aluminum in the silicon-aluminum mixed layer 57 is 81.5:18.5.
[0086] Comparative Example 1
[0087] This example is basically the same as Example 1, except that the number of layers and thickness settings of the composite structure are changed. The main differences are listed below:
[0088] In this example, the composite structure layer includes, from top to bottom, a base layer, a first niobium oxide layer, a first silicon dioxide layer, a second niobium oxide layer, and a second silicon dioxide layer.
[0089] Among them, the substrate layer is a PET layer with a thickness of 50μm; the primer layer is 0.1μm thick; the protective film is a PET protective film with a thickness of 100μm, and the protective film and the substrate are bonded together using primer; the HC layer is a polyurethane acrylic resin film layer with a thickness of 7μm.
[0090] The composite structure has 5 layers with a thickness of 57.8nm, of which the base material is silicon with a thickness of 0.6nm; the first niobium oxide layer has a thickness of 28.7nm, the first silicon dioxide layer has a thickness of 7.0nm; the second niobium oxide layer has a thickness of 15nm; and the second silicon dioxide layer has a thickness of 6.5nm.
[0091] Comparative Example 2
[0092] The difference between this comparative example and Example 1 is only in the arrangement of the composite structure layer, which is as follows:
[0093] The thickness of the composite structure layer in this example is 54.3nm, of which the base material is silicon with a thickness of 0.5nm; the thickness of the first niobium oxide layer is 23.6nm, the thickness of the first silicon dioxide layer is 5.1nm; the thickness of the second niobium oxide layer is 15nm; the thickness of the second silicon dioxide layer is 4.9nm, and the thickness of the third niobium oxide layer is 5.2nm.
[0094] The performance of the high-reflection and high-transmittance top coatings prepared in the examples and comparative examples was tested.
[0095] The relevant performance detection of the present invention adopts the following method:
[0096] Reflectivity: 1) Select a UV spectrophotometer as the test equipment, and ensure that the equipment has been calibrated and is in good working condition; 2) Cut the sample to be tested into a suitable size, and the sample surface is clean, flat, and free of scratches or pollution; 3) Set the test parameters: select the appropriate test wavelength, light source type, measurement angle and other parameters; 4) Place the sample to be tested in the test area, ensure that the sample is in close contact with the measuring head, ensure that the test environment is stable, and avoid interference from external light; 5) Start the equipment and start measuring reflectivity. The equipment will automatically record and display the measurement results.
[0097] Lab value: Lab value testing is a color description method based on the color space developed by CIE (International Commission on Illumination). It converts color from three-dimensional space (chromaticity, brightness, saturation) to two-dimensional space (Lab value). Through Lab testing, the specific values of the sample's transparency, color gamut, etc. can be ensured for comparative analysis.
[0098] Use UV spectrophotometer to perform Lab test on top coating; 1) Prepare samples: ensure that the sample surface is clean and flat, without interference from reflection or refraction; 2) Set test parameters: light source type, test band, observation angle, etc.; 3) Calibrate the instrument: ensure that the instrument is properly calibrated before testing to ensure the accuracy of the measurement results; 4) Place the sample: place the sample in the designated test area of the instrument, ensure that the sample is in close contact with the instrument measuring head to avoid interference from external light; 5) Start measurement: start the instrument for testing, 6) Record data.
[0099] Peel force: According to the JIS K5600 tape adhesion test standard, a 5KG tensile machine is used to perform a 90° tensile test on the sample. Wipe the test steel plate with an alcohol cloth, randomly cut a sample: 25.4mm wide and 120mm long, stick the sample on the steel plate and roll it back and forth once with a 2KG roller, and let it stand for 20 minutes. After the standing is completed, put the steel plate on the tensile machine to fix the fixture and sensor, and then start the test.
[0100] Reference Figure 2, is the reflectivity test result. It can be seen from the reflectivity spectrum curve that the reflectivity of the film in Example 3 is higher than that in Example 1 and Example 2, indicating that the design of the materials and thickness of each layer in the composite structure in Example 3 is beneficial to improving the reflectivity of the film.
[0101] Table 1 below shows the Lab value test results of the films prepared in the embodiments and comparative examples:
[0102] Table 1 Lab test data
[0103] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 L value 92.10 91.58 92.07 90.87 91.52 a value 0.11 0.09 0.05 0.63 0.84 b-value 0.18 0.13 0.10 2.12 1.95
[0104] The color characteristics and color difference of the film can be analyzed by Lab test to determine whether the color characteristics of the film meet the quality standards or whether there is a color difference problem in the preparation process. From the data comparison, it can be found that the b value of the film prepared in Comparative Example 1 and Comparative Example 2 is too large, indicating that there is a yellowing problem.
[0105] Table 2 below is a comparison of the peeling force data of optical films:
[0106] Table 2 Peel force test results
[0107] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Peel force / gf 1680.47 1695.45 1722.58 875.95 1346.95
[0108] It can be seen from Table 2 that when the PVD composite structure has niobium oxide as the outermost layer, the overall peel strength of the film is low due to the poor adhesion of niobium oxide to OCA.
[0109] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A high-reflection and high-transmittance top coating, characterized in that: It includes a protective film layer, a primer layer, a substrate layer, a printable HC layer, a composite structure layer, an OCA optical adhesive layer and a release film layer which are stacked in sequence from top to bottom.
2. The high-reflection and high-transmittance top coating according to claim 1, characterized in that: The composite structure layer is obtained by magnetron sputtering coating on the lower surface of the printable HC layer, and the composite structure layer includes a primer layer, a first niobium oxide layer, a first silicon dioxide layer, a second niobium oxide layer, a second silicon dioxide layer, a third niobium oxide layer and a silicon-aluminum mixed layer stacked in sequence from top to bottom; The molar ratio of silicon to aluminum in the silicon-aluminum mixed layer is 80-95:20-5.
3. The high-reflection and high-transmittance top coating according to claim 2, characterized in that: in, The total thickness of the composite structure layer is between 30nm and 100nm, and the refractive index is between 1.90 and 2.30; The thickness of the base layer is 0.1-1nm, the thickness of the first niobium oxide layer is 5-30nm, the thickness of the first silicon dioxide layer is 3-16nm, the thickness of the second niobium oxide layer is 5-20nm, the thickness of the second silicon dioxide layer is 3-10nm, the thickness of the third niobium oxide layer is 5-10nm, and the thickness of the silicon-aluminum mixed layer is 2-10nm.
4. The high-reflection and high-transmittance top coating according to claim 1, characterized in that: The selected protective film layer is a PET protective film with a thickness of 25 μm-100 μm; The thickness of the primer layer is 0.1 μm-0.9 μm.
5. The high-reflection and high-transmittance top coating according to claim 1, characterized in that: The substrate layer is selected from a PET layer, a PI layer, a TAC layer, a COP layer, and a PC layer; and the thickness of the substrate layer is 25-100 μm.
6. The high-reflection and high-transmittance top coating according to claim 1, characterized in that: The printable HC layer is a polyurethane acrylic resin film layer with a thickness of 1 μm-9 μm.
7. The high-reflection and high-transmittance top coating according to claim 1, characterized in that: The OCA optical adhesive layer is obtained by coating the OCA adhesive on the composite structure layer. The OCA adhesive comprises the following raw materials in parts by weight: 60-120 parts of acrylic prepolymer; 0.1-0.4 parts of a first photoinitiator; 0.1-0.3 parts of a leveling agent; 0.2-0.5 parts of a coupling agent; and 0.1-0.4 parts of a cross-linking agent.
8. The high-reflection and high-transmittance top coating according to claim 7, characterized in that: in, The acrylic prepolymer comprises the following raw materials in parts by weight: 45-75 parts of isooctyl acrylate; 15-35 parts of 2-hydroxyethyl acrylate; 5-22 parts of isobornyl acrylate; 5-15 parts of acrylic acid; 0.02-1 parts of a second photoinitiator; and 0.02-1 parts of a molecular weight regulator.
9. The high-reflection and high-transmittance top coating according to claim 1, characterized in that: The thickness of the OCA optical adhesive layer is 5 μm-50 μm; the thickness of the release film is between 100 μm-200 μm.
10. A method for preparing a high-reflection and high-transmittance top coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. A primer layer and a printable HC layer are respectively coated on the upper surface and the lower surface of the substrate layer, and a protective film layer is attached to the upper surface of the primer layer; S2. Using a magnetron sputtering coating process, selecting argon gas to bombard the target material, and sequentially coating a primer layer, a first niobium oxide layer, a first silicon dioxide layer, a second niobium oxide layer, a second silicon dioxide layer, a third niobium oxide layer and a silicon-aluminum mixed layer on the lower surface of the printable HC layer to form a composite structure layer; S3, coating the lower surface of the silicon-aluminum mixed layer of the composite structure layer with OCA glue, and forming an OCA optical glue layer after curing; S4, laminating a release film layer on the lower surface of the OCA optical adhesive layer to obtain the high-reflection and high-transmittance top coating.
Citation Information
Cited By
High-transmittance screen protection film with ultra-clear layered structure and preparation method of high-transmittance screen protection film
CN120173520A